Side-loading prevalence and intoxication in the night-time economy - Cameron M; Miller P; Roskruge M (Elsevier)
Although pre-drinking has attracted considerable research interest, side-loading (any drinking occurring outside of licensed premises during a night out, and excluding drinking at home) is comparatively under-studied. In this paper, we investigate the prevalence of side-loading behaviour and intoxication in the night-time economy of Hamilton, New Zealand's fourth-largest city. Using a street-intercept survey conducted over six nights (n = 469) in March and April 2019, we found that 17.5% of research participants (82/469), and 19.9% of drinkers (82/413), had engaged in side-loading. Of those engaging in side-loading, the majority did so in a car (61.0%), with smaller proportions engaging in side-loading in the street (17.1%), a carpark (12.2%), or somewhere else (13.4%). Men were significantly more likely than women to engage in side-loading behaviour (p = 0.001). In linear models controlling for time of the night, day of the week, and demographic variables, side-loading was not statistically significantly associated with breath alcohol content. This contrasts with pre-drinking, which was associated with statistically significantly higher breath alcohol content. Our results suggest that side-loading might not be used as a method for drinkers to enhance intoxication, but instead as a means of sustaining a target level of intoxication during an evening.
Keywords: Intoxication; New Zealand; Night-time economy; Pre-drinking; Side-loading; 1701 Psychology